Proposta de um modelo de ferramenta de tecnologia da Informação e comunicação (tic) que auxilie no processo de compras da UFSM - Negrini, Fernando (2016)
The purchasing area is one of the main activities of any public institution and of fundamental importance for the development of organizational activities. However, if these activities are not carried out in an integrated and clear way, the process will become inefficient, harming all the activities of the institution. Despite the importance of the theme for the Federal University of Santa Maria (UFSM), the purchasing process in the Institution is still fragmented, carried out through different applications of a software program and in other virtual environments, such as Internet sites, without integration between the stages of the process. This disintegration brings innumerable inefficiencies to management. In this way, Information and Communication Technologies (ICTs) emerge as a means to rationalize and integrate the process. This work aims to identify the requirements of a tool based on Information and Communication Technology (ICT) that helps in the UFSM purchasing process. The research had a predominantly quantitative approach, of a described character, of the case study type, and was developed at the Federal University of Santa Maria, more specifically in the area of purchases. For data collection, documentary research techniques, questionnaires and interviews were used. The analysis of the results made it possible to develop and analyze the mapping of the purchasing process, identify the degree of satisfaction and degree of difficulty of users in the use of existing ICT tools, and identify suggestions for improvement in ICT tools. From there, a model of ICT tool was proposed to assist in the UFSM purchasing process. This is expected to improve the process, contributing to a more efficient public management.